Neurons and Microglia; A Sickly-Sweet Duo in Diabetic Pain Neuropathy - Rajchgot, Trevor; Thomas, Sini Christine; Wang, Jo-Chiao; Ahmadi, Maryam; Balood, Mohammad; Crosson, Théo; Dias, Jenny Pena; Couture, Réjean; Claing, Audrey; Talbot, Sébastien (Frontiers in Neuroscience, 2019)
Diabetes is a common condition characterized by persistent hyperglycemia. High blood sugar primarily affects cells that have a limited capacity to regulate their glucose intake. These cells include capillary endothelial cells in the retina, mesangial cells in the renal glomerulus, Schwann cells, and neurons of the peripheral and central nervous systems. As a result, hyperglycemia leads to largely intractable complications such as retinopathy, nephropathy, hypertension and neuropathy. Diabetic pain neuropathy is a complex and multifactorial disease that has been associated with poor glycemic control, longer diabetes duration, hypertension, advanced age, smoking status, hypoinsulinemia, and dyslipidemia. While many of the driving factors involved in diabetic pain are still being investigated, they can be broadly classified as either neuron -intrinsic or -extrinsic. In neurons, hyperglycemia impairs the polyol pathway, leading to an overproduction of reactive oxygen species and reactive nitrogen species, an enhanced formation of advanced glycation end products, and a disruption in Na+/K+ ATPase pump function. In terms of the extrinsic pathway, hyperglycemia leads to the generation of both overactive microglia and microangiopathy. The former incites a feed-forward inflammatory loop that hypersensitizes nociceptor neurons, as observed at the onset of diabetic pain neuropathy. The latter reduces neurons’ access to oxygen, glucose and nutrients, prompting reductions in the number of nociceptor terminals and losses in sensation, as observed in the later stages of diabetic pain neuropathy. Overall, microglia can be seen as potent and long-lasting amplifiers of nociceptor neuron activity, and may, therefore, constitute a potential therapeutic target in the treatment of diabetic pain neuropathy.